Preterm births in Iceland 1997-2016: Preterm birth rates by gestational age groups and type of preterm birth - Áslaug Salka Grétarsdóttir 1974- (2019)
Introduction The frequency of preterm births has been increasing globally, mainly due to a rise in iatrogenic late preterm births. It is not well known if the prevalence of preterm births in Iceland has been following a similar trend. The aim of this study was to assess the prevalence of preterm births in Iceland during 1997-2016 by type of preterm birth. Methods This study included all live-births in Iceland during 1997-2016 identified from the Icelandic Medical Birth Registry. Rates of preterm births were calculated each year and stratified by gestational age groups and type of preterm birth. Risk of preterm birth by time period was assessed with Poisson regression models adjusted for demographic variables. Indications for iatrogenic births were identified using ICD-10 codes. Results The study population included 87,076 infants, of which 4,986 (5.7%) were preterm. The preterm birth rate increased from 5.3 to 6.1% (ARR=1.16, CI=1.07-1.26) between 1997-2001 to 2012-2016. The rate of late preterm births (of all births, 34w0d-36w6d), increased significantly: 3.7% to 4.5% (ARR=1.26, CI=1.15-1.40). The rate of iatrogenic preterm births (of all preterm births) doubled, from 20% in 1997-2001 to 43% in 2012-2016, even after adjustment for medical indications (ARR=2.40, CI=2.06-2.80). Spontaneous preterm births decreased during the study period (ARR=0.63, CI=0.56-0.72) and PPROMs increased slightly (ARR=1.31, CI=1.11-1.54). The largest contributing indication for iatrogenic births were fetal indications (26.2%), which decreased during the study period (32.6%-25.3%). Conclusions Preterm birth rates are low in Iceland, however increased slightly between 1997 and 2016. This may have been due to an increase in late and iatrogenic preterm births. The increase in iatrogenic preterm births remained significant after adjusting for medical indications for iatrogenic preterm births. This suggests that other factors than medical indications are affecting the rise in iatrogenic preterm births in Iceland. University of Iceland ...